Polyphenols Content and Antimicrobial, Antioxidant and Hemolytic Activities of Essential Oils from Four Selected Medicinal Plants Growing in Algeria - Halla, Noureddine; Boucherit, Kebir; Zeragui, Bankaddour; Djelti, Abdelkader; Belkhedim, Ziane; Hassani, Rachida; Benatallah, Saada; Djellouli, Hassiba; Kacimi, Oumlkheir; Boucherit-Otmani, Zahia (Biology, Medicine, & Natural Product Chemistry, 2020)
The Saharan and steppe spontaneous plants are very characteristic because of their particular adaptation to the desert and extreme environment. Some species have pharmacological properties that give them a medicinal interest. The aim of the present work was to determine the polyphenol contents of essential oils obtained from four endemic plants growing in Algeria (Pituranthos scoparius, Myrtus nivellei, Rosmarinus officinalis and Mentha piperita), and study its biological activity, including antimicrobial, antioxidant, and hemolytic. The antimicrobial activity was evaluated by the microdilution method against twelve strains. The antioxidant activity was carried out by two methods (DPPH radical scavenging and reducing power). However, the hemolytic effect has been evaluated against the red blood cells. P. scoparius and M. piperita showed yields of essential oils higher than 1%. All the strains showed sensitivity against the essential oils tested with the exception of the C. albicans treated by R. officinalis essential oils. The most sensitive strain was C. albicans treated by P. scoparius essential oils by MIC of 0.0781 mg/mL, it was the same plant that shows the highest polyphenol content (14.78 ± 0.72 g GAE/g DS). The antioxidant activity by the DPPH method was greater for all essential oils tested by IC50 ranging from 0.69 ± 0.07 (R. officinalis) to 30.67 ± 2.12 mg/mL (M. nivellei). The R. officinalis essential oils reported more antioxidant power than the positive control (ascorbic acid). In reducing iron, it was the R. officinalis essential oils which were found to be the most active with an EC50 concentration of 9.67 ± 1.36 mg/mL. After 120 min incubation, minimal haemolysis (10%) was obtained with essential oils of R. officinalis at a concentration of 0.39 mg/mL. We conclude that P. scoparius essential oils showed the high content of polyphenols and R. officinalis essential oils reported more antioxidant power than the positive control (ascorbic acid).